Designing a Peer-Support Application for Teenagers with Diabetes Type 1 - Adielsson, Linnéa; Hansson, Rebecka (My University, 2023)
Type 1 diabetes is an incurable disease affecting children, with 900 new cases diagnosed annually in Sweden. Managing diabetes is challenging for young people due to the need for constant blood sugar monitoring and strict treatment. This master thesis aims to design a smartphone app using a Human-centred design process and Research Through Design approach to address these challenges and provide peer support for teenagers with type 1 diabetes. The design process involved reviewing prior research, conducting interviews, user testing, and prototyping with teenagers, adolescents and parents. A high-fidelity prototype was developed, along with seven key factors for designing a peer-support app for teenagers with type 1 diabetes. While there may be additional factors to consider, this research emphasizes the importance of these factors as fundamental building blocks for future testing and research.
Keywords: diabetes type 1; user experience (UX); user interface (UI); user research; interaction design; prototyping; design process; evaluation; peer support